Porous ZnO/C microspheres prepared with maleopimaric acid as an anode material for lithium-ion batteries. (15th September 2020) - Song, Jungwook; Kim, Hanah; Jae, Woojin; Kim, Taejun; Futalan, Cybelle M.; Kim, Jongsik
Abstract: Zinc oxide (ZnO) is widely applied as an alternative anode material for lithium ion batteries due to its natural abundance, low cost, non-toxicity, and high theoretical capacity (978 mA h g −1 ). However, sluggish diffusion of lithium ions, poor electrical conductivity, and severe volume changes during continued cycles often result in low reaction kinetics and fast capacity fading. In this study, the synthesis of carbon coated ZnO microspheres is performed using maleopimaric acid, abietic acid, acetic acid, and stearic acid as both organic ligands and carbon sources. The influence of their molecular structure and number of carbon atoms on the electrochemical performance of ZnO electrodes is evaluated. In the voltage range of 0.01–3.0 V, ZnO particles prepared with maleopimaric acid display excellent cycling properties with a discharge capacity of 1044 mA h g −1 after 100 cycles at 0.1C and 516 mA h g −1 after 300 cycles at 1C. Results show that maleopimaric acid is also suitable in the fabrication of a binder-free ZnO electrode, which discharges a reversible capacity of 803 mA h g −1 at the 100th cycle with an excellent cycling retention. Graphical abstract: Image 1 Highlights: Porous ZnO/C microspheres is fabricated by maleopimaric acid as an organic ligand and a carbon source. Maleopimaric acid is a suitable organic ligand compared to rosin acid, acetic acid, and stearic acid. The ZnO/C sample exhibits outstanding electrochemical performance as an anode in lithium-ion batteries.